Aplicación de los principios de responsabilidad social en las empresas de participación de menos de diez empleados - Benito Hernández, Sonia; Esteban Sánchez, Pablo (REVESCO. Revista de Estudios Cooperativos, 2008)
We tend to associate the concept of social responsibility with large companies and multinationals, but the principles of social responsibility can and must be integrated into any organization, including micro-enterprises. This kind of company has some attributes that distinguishes them from big companies and derive some disadvantages when adopting principles and social responsibilities’ policies. However, they also present some advantages over large companies, which can be relied on in order to build social responsibility’s policies that influence positively on their performance and in managing its relations with the various operators with which it relates. This article identifies those strengths and weaknesses and proposes a framework and guidelines to address social responsibility within companies with less than 10 workers.